Análisis de los factores asociados a la formación de adherencias peritoneales en pacientes post laparatomizados como causa de oclusión intestinal - Escobedo Solis, Neil Eduardo (2016)
The present work is a study of 240 patients after abdominal surgery for laparotomy, 48 of whom developed bowel obstruction due to adhesions and post operative flanges, all emergency surgery at Regional Hospital of Trujillo between 2006 to 2011,where they tried to establish the factors associated with the formation of adhesions and corresponding flanges. Operative reports of all patients were reviewed and concluded that preoperative peritonitis, intraoperative bleeding and the absence of peritoneal lavage were the most significant factors associated with its pathogenesis, recommending in relation to the findings take the most appropriate measures to ensure barriers physical in an attempt to reduce the risk of adhesion formation and flanges